A DESCRIPTIVE STUDY OF PRONUNCIATION MASTERY - Isabella Rosalin; Wageyono; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
The purpose of this study is to learn about students' pronunciation skills, particularly in pronouncing short and long vowels. The research was descriptive quantitative in nature. The eight grade students, a total of 30 kids, are the focus of this study. The information is gathered using an oral test. The data was quantitatively analyzed to determine the percentage of students who scored well on pronunciation. The largest inaccuracy in the pupils' pronunciation was / æ /, which had a total percentage of 63,33% and was classed as moderate. To avoid mispronounce, the researcher proposed that teachers provide students the exact pronunciations. Students should practice more by using an online dictionary or other resources to assist them enhance their pronunciation skills.